2020
DOI: 10.1155/2020/8854068
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Application of the Linear Poisson Autoregressive Model for Analyzing the Dynamic Impact of Traffic Laws on Fatal Traffic Accident Frequency

Abstract: Annual fatal traffic accident data often demonstrate time series characteristics. The existing traffic safety analysis approaches (e.g., negative binomial (NB) model) often cannot accommodate the dynamic impact of factors in fatal traffic accident data and may result in biased parameter estimation results. Thus, a linear Poisson autoregressive (PAR) model is proposed in this study. The objective of this study is to apply the PAR model to analyze the dynamic impact of traffic laws and climate on the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Assessment of travel speed shows that vehicle transverse stability which includes the slippage and overturns determines the curve radius value to be selected when designing road horizontal curves [31]. Zhang computed the radius mean and curvature degree for all categories used in his research and then he regressed them against the mean of accident rates in every category, his findings supported some previous studies which found and stated that the curve sharpness has a significant impact on the accident rates [30].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Assessment of travel speed shows that vehicle transverse stability which includes the slippage and overturns determines the curve radius value to be selected when designing road horizontal curves [31]. Zhang computed the radius mean and curvature degree for all categories used in his research and then he regressed them against the mean of accident rates in every category, his findings supported some previous studies which found and stated that the curve sharpness has a significant impact on the accident rates [30].…”
Section: Introductionsupporting
confidence: 58%
“…Assessment using linear regression models showed unsatisfactory results as the properties of linear regression are normally distributed [27,28], which can generate negative or non-discrete values of accident rates [21]. Another model, Poisson models were suggested [29] and used by Zhang et al [30], for their consideration of random and sporadic data, in addition to easy estimation of variables relationships, however results can be overestimated or underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, volatility is caused by the uncertainty in the number of flights in each hour. For instance, some authors [42] have used the lineal Poison autoregressive (PAR) model as an alternative to the Poisson model to analyse the impacts of laws and climate on annual road traffic accidents. This alternative method may be applied in future work for comparative purposes.…”
Section: Methods: Modelling Efforts and Calibrationmentioning
confidence: 99%
“…A representative solution is to assess safety risks and formulate corresponding control strategies. On one hand, some researchers [9][10][11][12][13] investigated the effects of low visibility together with traffic parameters on the collision risk and developed real-time crash risk prediction models under fog conditions based on the historical data. Visibility is either a model input variable or a constraint in these models.…”
Section: Introductionmentioning
confidence: 99%